Investigation of carbon cathode surface before and after the passage of combined DC vacuum arc with superimposed high-current arc pulses - Zavaleyev, V.; Walkowicz, J.; Moszyński, D. (Вопросы атомной науки и техники, 2016)
The paper presents the results of studies of carbon cathode surface before and after the passage of the combined
DC vacuum-arc with superimposed high-current arc pulses. Investigations of surface morphology of carbon cathode
showed, that secondary nuclei of high-density are formed after passing of the combined DC-pulse vacuum-arc,
which results in the formation of a globular structures. The phase structure analysis by Raman spectroscopy showed
that even at a minimum operation time (5 s) of the combined DC-pulse vacuum-arc broadening of the peaks 1355
and 1583 cm⁻¹
occurs, which means that the carbon cathode surface undergo phase transformation. Results obtained
by XPS spectroscopy demonstrate that the globular structures formed on the cathode surface are composed of sp³-bonded carbon atoms and carbon-oxygen bonds. Представлены результаты исследования поверхности углеродного катода до и после прохождения
катодного пятна вакуумной дуги прямого тока в комбинации с наложенными сильноточными импульсами.
Исследования морфологии поверхности углеродного катода показали, что после прохождения катодного
пятна вакуумной дуги прямого тока в комбинации с сильноточными импульсами формируются вторичные
зародыши высокой плотности, в результате чего появляется глобулярная структура. Фазово-структурный
анализ с использованием раман-спектроскопии показал, что даже при минимальном времени работы (5 с)
вакуумной дуги происходит уширение пиков 1355 и 1583 см⁻¹, указывающее на то, что поверхность углеродного катода подвергается фазовым превращениям. Результаты, полученные ХР-спектроскопией,
показали, что глобулярные структуры, сформировавшиеся на поверхности катода, состоят из sр³ связанных атомов углерода и углеродакислорода. Представлені результати дослідження поверхні вуглецевого катода до і після проходження катодної
плями вакуумної дуги прямого струму в комбінації з накладеними сильноточними імпульсами. Дослідження
морфології поверхні вуглецевого катода показали, що після проходження катодної плями вакуумної дуги
прямого струму в комбінації з сильноточними імпульсами формуються вторинні зародки високої щільності,
внаслідок чого з'являється глобулярна структура. Фазово-структурний аналіз з використанням раман-
спектроскопії показав, що навіть при мінімальному часі роботи (5 с) вакуумної дуги відбувається
розширення піків 1355 і 1583 см⁻¹, що вказує на те, що поверхня вуглецевого катода піддається фазовим
перетворенням. Результати, отримані ХР-спектроскопією, показали, що глобулярні структури, що
сформувалися на поверхні катода, складаються з sр³ пов'язаних атомів вуглецю і вуглецю–кисню.